Childhood psychological abuse and relational aggression among adolescents: A moderated chain mediation model - Li, Ting; Huang, Yuhuai; Jiang, Meiru; Ma, Shutao; Ma, Yankun (Frontiers in Psychology, 2023)
Introduction Adolescents are in a period when a marked upward trend of adolescents relational aggression. Even though previous studies have found that childhood psychological abuse experience is an important factor influencing adolescent relational aggression, it is unclear when and under what circumstances childhood psychological abuse impacts adolescent relational aggression. This study constructed a moderated chain mediation model to investigate the influence of childhood psychological abuse on relational aggression among Chinese adolescents and its internal mechanism. Methods Data from 1868 (923 male and 945 female, M = 14.31, SD = 1.60) Chinese adolescents in two full-time middle schools in Guangzhou were collected via a cross-sectional survey in 2020. Adolescents reported on childhood psychological abuse, relational aggression, rejection sensitivity relational victimization and cognitive reappraisal. Results The results demonstrated that: (1) childhood psychological abuse was significantly positively related to relational aggression; (2) childhood psychological abuse was significantly linked with adolescents’ relational aggression through the separate mediating effects of rejection sensitivity and relational victimization, as well as through the chain mediating effects of rejection sensitivity and relational victimization; (3) the chain mediated effect of childhood psychological abuse on relational aggression through rejection sensitivity and relational victimization was moderated by cognitive reappraisal. Conclusion These findings indicate that childhood psychological abuse, as a kind of poor parenting style, has influence on adolescents’ internal personality (rejection sensitivity) and external behavior development (relational victimization and relational aggression). This study is helpful to demonstrate the protective effect of cognitive reappraisal and reveal the internal mechanism of childhood psychological abuse on relational aggression.